Women and Muslim Family Laws in Arab States : A Comparative Overview of Textual Development and Advocacy - Welchman, Lynn (2007)
A number of Arab states have recently either codified Muslim family law for the first time, or have issued amendments or new laws which significantly impact the statutory rights of women as wives, mothers and daughters. In Women and Muslim Family Laws in Arab States Lynn Welchman examines women's rights in Muslim family laws in Arab states across the Middle East while also surveying the public debates surrounding the issues. The author considers these new laws alongside older statutes to comment on the patterns and dynamics of change both in the texts of the laws, and in the processes through by which they are drafted and issued. She draws on original legal texts and explanatory statements as well as on extensive secondary literature particular to certain states for an insight into practice, and on; interventions by women's rights organizations and other parties to the debate in the press and in advocacy materials. The discussions are set in the contemporary global context that 'internationalises' the domestic and regional debates. The book considers laws in states from the Gulf to North Africa in regard to their approaches to issues of codification processes and issues of and of registration, capacity and guardianship in marriage, polygyny, the marital relationship, divorce and child custody. It has a full bibliography and includes an annex providing translated extracts of the laws under examination. Welchman richt zich in Women and Muslim Family Laws in Arab States op de rechten van de vrouw binnen het islamitische familierecht in Arabische landen. Welchman analyseert hoe het familierecht is vastgelegd in wetboeken en de publieke debatten die daaruit voortkomen. In de afgelopen decennia is het islamitische familierecht in een aantal landen voor het eerst vastgelegd of zijn belangrijke wijzigingen doorgevoerd. De auteur bespreekt deze nieuwe wetten in het licht van oudere statuten om de dynamiek van het islamitische familierecht te duiden. Zij beroept zich niet alleen op juridische bronnen, maar schenkt ook ruim aandacht aan de juridische praktijk. Door de reacties van vrouwenrechtenorganisaties, media en juristen te analyseren, wijst ze op controversiële kwesties. Bijzonder aan dit boek is de internationale en vergelijkende benadering. De auteur bestudeert discussies rondom huwelijk, polygamie, scheiding en voogdij vanuit het perspectief van verschillende landen. Nationale debatten worden op deze manier geplaatst in een mondiale context. Het boek beschikt over een volledige bibliografie en bijlagen met vertalingen van de behandelde wetsfragmenten.